Integrating Trust and Engagement to Improve Customer Experience: Advancing Trust Commitment within the Context of Chatbot Industry - Andaresti, Sherly Indira; Marsasi, Endy Gunanto (MEC-J (Management and Economics Journal), 2025)
This study aims to analyze the factors that influence user experience in using chatbot services, focusing on the role of information quality, service quality, commitment, trust, and engagement. This study adds engagement variables as a novelty in this study. The primary theory in this work is trust commitment theory. Purposive sampling, which yields 300 samples, is used in this study's quantitative methodology. This study uses Structural Equation Modeling (SEM) analysis with the help of Amos Graphic software as a data processing tool. The results of the study indicate that information quality and service quality have a significant positive effect on user trust and engagement. In addition, user commitment also has a significant effect on user experience, as well as trust which plays an important role in improving user experience on chatbot services. This study provides important insights for chatbot service providers in improving service quality to increase trust, engagement, and user experience.